INFLUENCE OF GIBBERELLIC ACID AND PLANT GEOMETRY ON GROWTH, FLOWERING AND CORM PRODUCTION IN GLADIOLUS (GLADIOLUS GRANDIFLORUS) UNDER JAMMU AGROCLIMATE - SHEETAL DOGRA; R K PANDEY; DEEP JI BHAT (International Journal of Pharma and Bio Sciences, 2012)
The present investigation was conducted to study the effect of gibberellic acid and plant geometry on growth, flowering and corm production in gladiolus cv. ‘Novalux’ under Jammu conditions. Four concentrations of GA3 (0, 100, 200 and 300 ppm) and three levels of spacing (20x40cm, 30x40cm and 40x40 cm) were tested in Factorial RBD with three replications. The analyzed data indicated that maximum plant height, number of leaves, leaf width, spike length, rachis length, corm diameter, corm weight and early flowering was recorded at 300 ppm GA3. Corms planted at a spacing of 40x40cm exhibited highest plant height, rachis length, number of florets per spike, floret diameter, number of corms per plant, corm diameter, corm and cormel weight. Among interactions, treatment of corms with 300ppm GA3 and spacing at 40x40 cm was found more effective in the enhancement of vegetative and floral attributes.